Network advantage: Uncontested structural holes and organizational performance in market crises - Shipilov, Andrew; Li, Stan X.; Bothner, Matthew S.; Truong, Nghi (Strategic Management Journal, 2023)
Abstract Research Summary We examine how crisis conditions affect the link between structural holes and organizational performance. Since brokerage offers early access to diverse perspectives and autonomy in exchange relations, the benefits of brokerage should rise when crises erupt. However, evidence on the subject has been inconclusive, raising the question of whether crisis actually imposes a boundary condition on structural hole theory. Using longitudinal data on investment banks, and exploiting the 2000 dot.com crisis as well as the 2008 financial crisis, we explore whether crises moderate the favorable effect of brokerage on performance. Our results reveal that only exclusive, and not shared, structural holes are advantageous for performance, as they facilitate ambidextrous responses to crisis. Implications for brokerage theory and new research on crisis are discussed. Managerial Summary Crises, in the form of pandemics, wars, or market crashes, affect the relationship between a firm's position in collaboration networks and its future performance. Our analyses bring into focus a finding of interest to managers of firms operating as brokers in these networks: when a crisis erupts, a firm that serves as the sole bridge between its otherwise disconnected collaborators performs especially well. Uncontested by other intermediaries, such firms achieve a better mix of search and stability, and thus higher performance, amidst crisis. These advantages disappear when other intermediaries are present. This implies that firms frequently exposed to crisis may benefit from constructing entry barriers around their bridging positions in collaboration networks.